Prognostic factors and treatment comparison in small cell neuroendocrine carcinoma of the uterine cervix based on population analyses - Li‐mei Lin; Qin Lin; Jun Liu; Ke‐xin Chu; Yun‐Xia Huang; Zong‐Kai Zhang; Tao Li; Ya‐Qing Dai; Jin‐Luan Li (Cancer Medicine, 2020)
Abstract Objective We aimed to assess the impact of the treatment modality on the outcome of small cell neuroendocrine cervical carcinoma (SCNEC) using the Surveillance Epidemiology and End Results (SEER) database. Methods Patients from the SEER program between 1981 and 2014 were identified. Significant factors for cancer‐specific survival (CSS) and overall survival (OS) were analyzed using the Kaplan‐Meier survival and Cox regression methods. Results A total of 503 SCNEC patients were identified. The 5‐year CSS and OS were 36.6% and 30.6%, respectively. The International Federation of Gynecology and Obstetrics (FIGO) stage I to IV distributions was 189 (37.6%), 108 (21.5%), 95 (18.9%), and 111 patients (22.0%), respectively. Within the patients with known treatment strategies, 177 (45.9%) were treated with radical surgery and 209 (54.1%) underwent primary radiotherapy. Local treatment strategies were independent prognostic factor for CSS and OS. The 5‐year CSS for radical surgery and primary radiotherapy was 50.0% and 27.9%, respectively (P < .001). The 5‐year OS for those who received radical surgery and primary radiotherapy was 57.8%, and 29.6%, respectively (P < .001). In FIGO stage I SCNEC, patients treated with radical surgery had superior CSS (P = .001) and OS (P = .003) than those with primary radiotherapy. However, in FIGO stage II and III SCNEC, there were no differences in CSS and OS with respect to different local treatment strategies. Our results also found that the addition of brachytherapy impacted OS in the FIGO stage III SENCE (P = .002). The 5‐year CSS and OS of patients with FIGO IV were only 11.7% and 7.1%, respectively. Conclusions SCNEC is a rare disease with aggressive clinical behavior. The findings indicate that radical surgery should be suggested for early‐stage SCNEC and combining radiation therapy with brachytherapy should be suitable for patients with advanced stage.